Prediction of positive social behaviors based on norm-activation model in female students - Mahin Nazari; Zahra Pakizehpour; Mohammad Hossein Kaveh; Sareh keshavarzi (Gonabad University of Medical Sciences, 2017)
Keeping order in the classroom, modifying students' behavioral problems, and implementing regulations codified at schools are among the issues in education involving the minds of headmasters and teachers. Following adolescence appropriate behavioral patterns plays a key role in bringing about the adolescents' positive social behavior. This study aimed to investigate the predictors of adolescents' positive social behavior using the Norm Activation Model (NAM). This study was conducted on 200 female students between 12 and 13 years old studying in the third educational district of Shiraz, Iran, that were selected through cluster random sampling method. The study data were collected as self-report using a questionnaire composed of demographic items and items measuring positive social behavior based on NAM. The findings showed that among the NAM constructs, personal norm was the strongest predictor of positive social behavior followed by awareness of consequences and ascription of responsibility. The relation of awareness of consequences to birth order, ascription of responsibility to father's occupation and birth order, personal norm to father's occupation, number of brothers, and birth order, and positive social behavior to number of brothers, birth order, non-classmate friends, and number of intimate non-classmate friends was statistically significant. It was concluded that NAM could be utilized to predict the factors affecting positive social behavior. Moreover, the results can be used by authorities and policymakers to develop appropriate plans and behavioral interventions.